The Inachoididae spider crabs (Crustacea, Brachyura) from the Neogene of the tropical Americas. (March 2022) - Lima, Daniel; Aguilera, Orangel; Tavares, Marcos
Abstract: The spider crabs Willinachoides santanai n. gen. n. sp. from the early-middle Miocene of north Brazil and Paradasygyius rodriguezi n. sp. from the late Miocene of Venezuela are described and illustrated. Additionally, Eoinachoides senni Van Straelen, 1933, from the late Oligocene–early Miocene of Venezuela, is redescribed based on photographs of the holotype, and the diagnosis of Eoinachoides latispinosus Carriol, Muizon, and Secretan, 1987, from the late Miocene of Peru, is emended also on the basis of photographs of the holotype. The past distribution points to a Tethyan background for the current amphi-American Inachoididae, with the oldest fossil species known from the early Eocene Tethyan regions (Pakistan and Italy), and from the late Eocene–late Pliocene of the Americas. The high number of monotypic genera in Inachoididae could be the result of rapid dispersion followed by diversification during the Neogene of the tropical America, facilitated by global and regional events (e.g., eustatic sea level changes, the Mi-1 Oligocene-Miocene boundary global cooling, the global warming period of the Middle Miocene Climate maximum, closure of the Panama Isthmus, and marine incursions into the Amazon Basin). The shoaling and final closure of the Central American Seaway are thought to have critically affected the evolution of the inachoidids and shaped their current distribution patterns. UUID: http://zoobank.org/6275fdc4-4bfa-4873-9320-3143d4915172 .